2022
DOI: 10.37284/eajenr.5.1.862
|View full text |Cite
|
Sign up to set email alerts
|

An Invasive Plant Parthenium hysterophorus Reduces Native Forage Cover

Abstract: While some research has been conducted in sub–Saharan Africa on the alien invasive Parthenium hysterophorus, little work has assessed whether it is poses negative impact on native forages. A field survey was carried out to study the dominant co–existing plant species, and its impact on plant abundance, species, and native forage cover. We found that non–natives were the dominant co–existing plants with P. hysterophorus compared to natives. Plant species (r = -0.889, P = 0.043) and abundance (r = -0.968, P = 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…In the current study, analyses of the diversity indices between the invaded and control plots showed noticeable changes in the diversity of the plants. These findings are in line with those of Riaz and Javaid (2011), Shabbir and Bajwa (2007), Ojija et al (2021) and Ojija & Lutambi (2022) all of which report changes in the vegetation composition of the invaded plots. Crop output, biodiversity, and human and animal health are all impacted by parthenium (Shabbir, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, analyses of the diversity indices between the invaded and control plots showed noticeable changes in the diversity of the plants. These findings are in line with those of Riaz and Javaid (2011), Shabbir and Bajwa (2007), Ojija et al (2021) and Ojija & Lutambi (2022) all of which report changes in the vegetation composition of the invaded plots. Crop output, biodiversity, and human and animal health are all impacted by parthenium (Shabbir, 2013).…”
Section: Discussionsupporting
confidence: 91%